Battery cell, battery device, and electric device
Patent Information
- Application Number
- CN202610069740.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]相关技术中的电池单体无法兼顾充电性能以及循环性能
[0051] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application.
Smart Images

Figure CN122931044A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a battery cell, a battery device, and an electrical device. Background Technology
[0002] Energy conservation and emission reduction are key to sustainable social development. Rechargeable batteries, with their ability to store and release energy as needed, are widely used in various electrical devices and energy storage systems, and are an important component in promoting energy transition and sustainable development. For the new energy industry, battery technology is a crucial factor in its development.
[0003] The battery cells in the related technologies cannot simultaneously achieve both charging performance and cycle performance. Summary of the Invention
[0004] This application aims to at least solve one of the technical problems existing in the background art. Therefore, one object of this application is to provide a battery cell, a battery device, and an electrical device that improves both the charging performance and cycle performance of the battery cell.
[0005] An embodiment of the first aspect of this application provides a battery cell including an electrode assembly and an electrolyte, wherein the electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode; The electrolyte comprises an electrolyte salt, which includes lithium fluorosulfonyl imide, and the lithium fluorosulfonyl imide accounts for 3%-8.5% of the total mass of the electrolyte. The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer, and the second negative electrode film layer is disposed between the negative current collector and the first negative electrode film layer. The first negative electrode film layer includes a first graphite, and the median ID / IG ratio L50 of the first graphite is 0.3-0.55. The second negative electrode film layer includes a second graphite, and the median ID / IG ratio L50 of the second graphite is 0.05-0.2. Along the height direction of the battery cell, the size of the negative electrode film is greater than or equal to 140 mm, and the height direction is parallel to the direction of gravity.
[0006] To achieve higher energy density and pack efficiency in the battery system, this application adopts a high-height negative electrode film design with a dimension ≥140mm along the gravity direction of the individual battery cells. To improve vehicle operating efficiency and achieve ultra-fast recharging, graphite with a large ID / IG ratio can be used in the negative electrode, providing more lithium intercalation active sites and improving interfacial mass transfer efficiency. However, if all negative electrodes use graphite with a large ID / IG ratio, on the one hand, graphite with a large ID / IG ratio has more lattice defects, resulting in poor formation of the negative electrode electrolyte interphase (SEI) film. Repeated formation and repair of the SEI film will consume active lithium. On the other hand, the reduced orderliness of the negative electrode graphite will affect the bulk diffusion of lithium ions in the graphite, increasing polarization. Simultaneously, the lithium ion solvation effect is amplified, causing lithium ions to co-intercalate with solvent molecules between graphite layers during lithium ion insertion, leading to graphite stripping during cycling and reducing the cycle life of the individual battery cells. Many defects in graphite lead to low mechanical strength. During the lithium-ion insertion and extraction process, the expansion and contraction of the graphite lattice causes stress concentration and cracks, which in turn damage the conductive network, increase polarization, and cause some graphite particles to lose electrical contact with the electrode, becoming "dead carbon". It also creates new, unstable surfaces, continuously consuming electrolyte and lithium source to form a new SEI film, resulting in accelerated cycle life decay.
[0007] This application utilizes a fast-charging first graphite with a large ID / IG ratio in the upper layer and a second graphite with a smaller ID / IG ratio in the lower layer. This material has a high degree of graphitization, an ordered and dense crystal structure, high mechanical strength, and isotropic expansion characteristics. This allows it to effectively buffer and disperse the macroscopic mechanical stress generated by the fast-charging reaction in the upper layer and the overall axial expansion difference, suppressing the overall warping of the electrode and the macroscopic propagation of particle cracks. The stable and dense crystal surface makes it easier to form a thin and stable negative electrode electrolyte interface film (SEI film), which significantly reduces the continuous consumption of active lithium and electrolyte during cycling, improves the reliability of the bottom of the high electrode component (high polarization risk area), and provides a guarantee for long-term cycling. Meanwhile, this application incorporates lithium fluorosulfonylimide into the electrolyte. The large anionic radius of lithium fluorosulfonylimide effectively weakens the solvation sheath binding energy of lithium ions, promotes the desolvation process of lithium ions before intercalation, and significantly inhibits the co-intercalation of solvent molecules between graphite layers. In particular, it protects the upper first graphite layer with a high ID / IG ratio, avoiding its rapid stripping due to co-intercalation and compensating for its structural weaknesses. In addition, the SEI film formed by this salt is rich in inorganic substances such as LiF, exhibiting excellent compactness, mechanical flexibility, and thermal stability. It adheres tightly to the surface of graphite particles, making it suitable for cycling (especially the upper layer). The volume expansion and contraction of the upper fast-charging graphite layer reduces SEI film rupture and the resulting "patchwork" repair consumption; it uniformly covers the surface of the lower highly ordered graphite layer, further consolidating its already stable interface and reducing side reactions; it enhances the stability of the SEI film at high temperatures, directly compensating for the shortcomings of the upper fast-charging graphite layer intensifying interface side reactions during high-temperature cycling, and improving the environmental adaptability of the battery cell; the addition of lithium fluorosulfonylimide also helps to improve the electrolyte ionic conductivity and, to some extent, alleviates the concentration polarization caused by excessively long ion transport distance in high-energy cells, further improving the cycle life of the battery cell.
[0008] In some embodiments, the specific surface area of the first graphite is smaller than that of the second graphite. Therefore, the first graphite has a relatively smaller number of active sites, which reduces side reactions between the first graphite and the electrolyte, while the second graphite has a relatively larger number of active sites, which improves lithium storage capacity, thus balancing the cycle life and charging performance of the battery cell.
[0009] In some embodiments, the specific surface area of the first graphite is 0.8 m². 2 / g-1.0m 2 / g.
[0010] In some embodiments, the specific surface area of the second graphite is 1.9 m². 2 / g-2.1m 2 / g.
[0011] With the specific surface areas of the first and second graphite within the aforementioned range, on the one hand, side reactions between the first graphite and the electrolyte can be reduced; on the other hand, the number of active sites on the surface of the second graphite can be increased, thereby improving the rate of lithium-ion insertion into the graphite and thus balancing the cycle life and kinetic performance of the battery cell.
[0012] In some embodiments, at least a portion of the surface of the first graphite comprises a carbon material. By coating the graphite surface with a carbon material, the specific surface area of the first graphite can be reduced, thereby reducing side reactions between the graphite and the electrolyte and balancing the charging performance and cycle life of the battery cell.
[0013] In some embodiments, the mass percentage of carbon element is 2%-4% based on the total weight of the first negative electrode film layer.
[0014] In some embodiments, the volume average particle size Dv50 of the first graphite is smaller than the volume average particle size Dv50 of the second graphite.
[0015] In some embodiments, the volume average particle size Dv50 of the first graphite is 10 μm-13 μm.
[0016] In some embodiments, the volume average particle size Dv50 of the second graphite is 14 μm-16 μm.
[0017] The first type of graphite has a small average particle size, which can shorten the lithium-ion diffusion path, increase the lithium-ion migration rate, and thus improve the charging performance of the battery cell. The second type of graphite has a large average particle size, which can increase the compaction density and mechanical strength of the negative electrode film. It can effectively buffer and disperse the macroscopic mechanical stress generated by the upper fast charging reaction and the overall axial expansion difference, suppress the phenomenon of overall electrode warping after the size of the negative electrode film increases, improve the cycle performance of the battery cell, and take into account the energy density of the battery cell.
[0018] In some embodiments, the compaction density of the negative electrode film is 1.65 g / cm³. 3 -1.75g / cm 3 This can increase the energy density of individual battery cells.
[0019] In some embodiments, the areal density of the negative electrode film layer on one side is 0.135 g / 1540.25 mm. 2 -0.17g / 1540.25mm 2 When the unilateral density of the negative electrode film is within the above-mentioned range, the transport distance of lithium ions in the negative electrode film can be reduced, which is beneficial to improving the charging performance of the battery cell while taking into account the energy density of the battery cell.
[0020] In some embodiments, the thickness of the negative electrode film layer on one side is 50 μm-70 μm. This improves the charging performance of the battery cell at room temperature. The thickness of the negative electrode film layer on one side within the above range reduces the transport distance of lithium ions within the negative electrode film layer, which is beneficial for improving the charging performance of the battery cell.
[0021] In some embodiments, the thickness of the first negative electrode film layer on one side is 25μm-35μm.
[0022] In some embodiments, the thickness of the second negative electrode film layer on one side is 25μm-35μm.
[0023] By keeping the thicknesses of the first and second negative electrode films within the aforementioned range, the transport path of lithium ions in the negative electrode films can be shortened, thereby improving the fast-charging performance of the battery cell while also maintaining energy density.
[0024] In some embodiments, the size of the negative electrode film layer is 140mm-350mm along the height direction of the battery cell.
[0025] In some embodiments, the negative electrode film layer comprises carbon nanotubes. The high aspect ratio and three-dimensional network structure of carbon nanotubes can form a conductive framework that runs through the negative electrode film layer, reducing the expansion and contraction deformation of graphite, reducing the accumulation of internal stress in the negative electrode sheet, and improving the problem of lifespan degradation due to expansion of the negative electrode sheet during cycling.
[0026] In some embodiments, the carbon nanotubes account for 0.01%-0.1% of the total mass of the negative electrode film. This improves electrode expansion and enhances the cycle performance of the battery cell.
[0027] In some embodiments, the specific capacity of the negative electrode film is 354 mAh / g-360 mAh / g. Therefore, the lithium intercalation in the negative electrode film is relatively sufficient, resulting in a high specific capacity of the negative electrode material, which can improve the capacity and cycle life of the battery cell. In some embodiments, the lithium fluorinated sulfonylimide comprises one or both of lithium bisfluorosulfonylimide and lithium bistrifluoromethylsulfonylimide. Thus, both types of lithium fluorinated sulfonylimide can improve the cycle performance of a single battery cell.
[0028] In some embodiments, the lithium fluorosulfonylimide comprises 4%-7% of the total mass of the electrolyte. A mass percentage of lithium fluorosulfonylimide within this range can improve the high-temperature cycle performance of the battery cell.
[0029] In some embodiments, the electrolyte salt further includes lithium hexafluorophosphate. Lithium hexafluorophosphate is more easily dissociated, which can improve the ionic conductivity of the electrolyte and enhance the charging capability of the battery cell at room temperature.
[0030] In some embodiments, the lithium hexafluorophosphate accounts for 8%-13.5% of the total mass of the electrolyte.
[0031] In some embodiments, the electrolyte comprises a carbonate solvent, including one or more of ethylene carbonate, propylene carbonate, butenyl carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate. This improves the electrolyte's ability to dissociate electrolyte salts, increases the electrolyte's ionic conductivity, and enhances the charging capability of the battery cell at room temperature.
[0032] In some embodiments, the carbonate solvent accounts for 70%-85% of the total mass of the electrolyte.
[0033] In some embodiments, the electrolyte includes an additive, which includes one or more of vinylene carbonate, fluoroethylene carbonate, trimethyl phosphate, dimethyl methyl phosphate, and biphenyl.
[0034] Ethylene carbonate and fluoroethylene carbonate can form a stable SEI film on the graphite surface, reducing side reactions between the electrolyte and graphite and improving the cycle life of the battery cell.
[0035] Trimethyl phosphate (TMP) captures active protons through phosphorus-containing active particles, inhibiting the thermal decomposition of organic solvents and significantly improving the thermal stability of the electrolyte. It also forms a protective film on the electrode surface, enhancing cycle performance. Dimethyl methyl phosphate (DMP) is a flame retardant additive that significantly improves the thermal stability of the electrolyte through its phosphorus content.
[0036] When a battery cell is overcharged, biphenyl can undergo a polymerization reaction on the surface of the positive electrode, thereby forming a polymer film and generating gas on the surface of the positive electrode active material. This triggers the internal pressure valve of the battery cell to open prematurely, reducing the risk of thermal runaway caused by continuous overcharging and improving the safety of the battery cell.
[0037] In some embodiments, the conductivity of the electrolyte at 25°C is 9 mS / cm-13 mS / cm. This improves the lithium-ion migration rate and enhances the charging performance of the battery cell.
[0038] In some embodiments, the electrolyte injection coefficient of the battery cell is 2.5 g / Ah-2.8 g / Ah.
[0039] Battery cells with an electrolyte injection coefficient within the above range can keep the side reactions between carbonate solvents and negative electrode active materials at a low level, thus ensuring the battery's cycle life; they can also improve the wettability between the electrolyte and the electrode, reduce the battery interface resistance, decrease the battery impedance, and further improve the battery's charging performance.
[0040] In some embodiments, the separator includes: a base membrane; a first functional layer located on at least one side of the base membrane, the first functional layer comprising inorganic particles; and a second functional layer located on the side of the first functional layer away from the base membrane, the second functional layer comprising an adhesive. This reduces the contact angle of the electrolyte at the separator-negative electrode interface, further improving electrolyte wettability. This increases the electrolyte absorption capacity at the top of the battery cell while simultaneously increasing the concentration of electrolyte salts in the electrolyte at the top of the battery cell, thereby further improving the cycle life of the battery cell.
[0041] In some embodiments, the inorganic particles include one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide. This improves the wettability of the electrolyte to the separator membrane and enhances the electrolyte retention capacity of the electrode assembly.
[0042] In some embodiments, the binder comprises a fluoropolymer, which includes one or more of polyvinylidene fluoride, polychlorotrifluoroethylene, and polytetrafluoroethylene. Thus, the fluoropolymer can provide suitable adhesion, ensuring stable bonding of the positive electrode, separator, and negative electrode, while preventing shrinkage at high temperatures and powder shedding during cycling, thereby improving the cycle performance of the battery cell.
[0043] In some embodiments, the average particle size of the fluoropolymer particles is 7 μm-15 μm.
[0044] The average particle size of the fluoropolymer particles is within the above range, which can prevent the agglomeration of small-sized inorganic particles, make the inorganic particles uniformly distributed around the binder particles, significantly improve the capillary effect of the functional layer of the separator, and enhance the wettability of the electrolyte to the separator.
[0045] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes one or more lithium phosphates and their modified compounds. This improves the safety and cycle performance of the battery cell.
[0046] In some embodiments, the lithium-containing phosphate includes one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate.
[0047] In some embodiments, the areal density of the positive electrode film layer on one side is 0.33 g / 1540.25 mm². 2 -0.36g / 1540.25mm 2 This increases the energy density of individual battery cells.
[0048] In some embodiments, the compaction density of the positive electrode film is 2.7 g / cm³. 3 -2.8g / cm 3 This increases the energy density of individual battery cells.
[0049] An embodiment of the second aspect of this application provides a battery device including the battery cell in the above embodiments, the battery device including one or more of the following: battery module, battery pack, and energy storage battery.
[0050] An embodiment of the third aspect of this application provides an electrical device including the battery device described in the above embodiments, the battery device being used to provide electrical energy.
[0051] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0052] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 This is a schematic diagram of a battery cell according to one embodiment of this application.
[0053] Figure 2 yes Figure 1 An exploded view of a battery cell according to one embodiment of this application is shown.
[0054] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0055] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0056] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.
[0057] Figure 6 This is a schematic diagram of an electrical device in which a battery is used as a power source according to one embodiment of this application.
[0058] Explanation of reference numerals in the attached figures: 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Battery; 51 Housing; 52 Electrode assembly; 53 Cover plate. Detailed Implementation
[0059] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0061] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0062] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. In the description of the embodiments of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0063] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0064] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0065] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0066] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0067] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0068] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0069] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0070] Currently, the application of rechargeable batteries is becoming increasingly widespread, judging from market trends. They are not only used in energy storage systems for hydropower, thermal power, wind power, and solar power plants, but also extensively in various electronic devices, such as electric bicycles, electric motorcycles, and electric vehicles, as well as in military equipment and aerospace. As the application areas of rechargeable batteries continue to expand, the market demand is also constantly increasing.
[0071] As battery technology continues to develop, the demand for comprehensive battery performance is gradually increasing, and the core direction of battery technology development is to achieve an efficient balance among various performance characteristics.
[0072] An embodiment of the first aspect of this application provides a battery cell, including an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrode. The electrolyte includes an electrolyte salt, which includes lithium fluorosulfonylimide. Based on the total mass of the electrolyte, the mass percentage of the lithium fluorosulfonylimide is 3%-8.5%. The negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer, which is disposed between the negative current collector and the first negative electrode film layer. The first negative electrode film layer includes a first graphite, and the median ID / IG median L50 of the first graphite is 0.3-0.55. The second negative electrode film layer includes a second graphite, and the median ID / IG median L50 of the second graphite is 0.05-0.2. Along the height direction of the battery cell, the size of the negative electrode film layer is greater than or equal to 140 mm, and the height direction is parallel to the direction of gravity.
[0073] To achieve higher energy density and pack efficiency in the battery system, this application adopts a high-height negative electrode film design with a dimension ≥140mm along the gravity direction of the individual battery cells. To improve vehicle operating efficiency and achieve ultra-fast recharging, graphite with a large ID / IG ratio can be used in the negative electrode, providing more lithium intercalation active sites and improving interfacial mass transfer efficiency. However, if all negative electrodes use graphite with a large ID / IG ratio, on the one hand, graphite with a large ID / IG ratio has more lattice defects, resulting in poor formation of the negative electrode electrolyte interphase (SEI) film. Repeated formation and repair of the SEI film will consume active lithium. On the other hand, the reduced orderliness of the negative electrode graphite will affect the bulk diffusion of lithium ions in the graphite, increasing polarization. Simultaneously, the lithium ion solvation effect is amplified, causing lithium ions to co-intercalate with solvent molecules between graphite layers during lithium ion insertion, leading to graphite stripping during cycling and reducing the cycle life of the individual battery cells. Many defects in graphite lead to low mechanical strength. During the lithium-ion insertion and extraction process, the expansion and contraction of the graphite lattice causes stress concentration and cracks, which in turn damage the conductive network, increase polarization, and cause some graphite particles to lose electrical contact with the electrode, becoming "dead carbon". It also creates new, unstable surfaces, continuously consuming electrolyte and lithium source to form a new SEI film, resulting in accelerated cycle life decay.
[0074] This application utilizes a fast-charging first graphite with a large ID / IG ratio in the upper layer and a second graphite with a smaller ID / IG ratio in the lower layer. This material has a high degree of graphitization, an ordered and dense crystal structure, high mechanical strength, and isotropic expansion characteristics. This allows it to effectively buffer and disperse the macroscopic mechanical stress generated by the fast-charging reaction in the upper layer and the overall axial expansion difference, suppressing the overall warping of the electrode and the macroscopic propagation of particle cracks. The stable and dense crystal surface makes it easier to form a thin and stable SEI film, significantly reducing the continuous consumption of active lithium and electrolyte during cycling, improving the reliability of the bottom of the high-electrode component (high polarization risk area), and providing a guarantee for long-term cycling. Meanwhile, this application incorporates lithium fluorosulfonylimide into the electrolyte. The large anionic radius of lithium fluorosulfonylimide effectively weakens the solvation sheath binding energy of lithium ions, promotes the desolvation process of lithium ions before intercalation, and significantly inhibits the co-intercalation of solvent molecules between graphite layers. In particular, it protects the upper first graphite layer with a high ID / IG ratio, avoiding its rapid stripping due to co-intercalation and compensating for its structural weaknesses. In addition, the SEI film formed by this salt is rich in inorganic substances such as LiF, exhibiting excellent compactness, mechanical flexibility, and thermal stability. It adheres tightly to the surface of graphite particles, making it suitable for cycling (especially the upper layer). The volume expansion and contraction of the upper fast-charging graphite layer reduces SEI film rupture and the resulting "patchwork" repair consumption; it uniformly covers the surface of the lower highly ordered graphite layer, further consolidating its already stable interface and reducing side reactions; it enhances the stability of the SEI film at high temperatures, directly compensating for the shortcomings of the upper fast-charging graphite layer intensifying interface side reactions during high-temperature cycling, and improving the environmental adaptability of the battery cell; the addition of lithium fluorosulfonylimide also helps to improve the electrolyte ionic conductivity and, to some extent, alleviates the concentration polarization caused by excessively long ion transport distance in high-energy cells, further improving the cycle life of the battery cell.
[0075] The direction of gravity can be the direction of gravity of the battery cell when the electrical device is in use, or the direction of gravity of the battery cell when it is mounted on the electrical device. For example, when the vehicle is parked on a level surface, the direction of gravity of the battery cell is the direction of its height. As an example, Figure 1 The Z-direction is the direction of gravity and also the height direction of the individual battery cells.
[0076] ID / IG is the ratio of the intensity of the D peak to the intensity of the G peak obtained from the Raman spectrum. ID represents the Raman spectrum at 1350±100 cm⁻¹. -1 The intensity of peak D at 1580 ± 100 cm⁻¹, IG represents the Raman spectrum at 1580 ± 100 cm⁻¹. -1 The intensity of the G peak at that location.
[0077] In this application, the median ID / IG of graphite can be tested using the following method: After discharging the battery cell to 0% SOC, disassemble the battery cell to obtain the negative electrode sheet. Use CP-SEM to observe the cross-section of the electrode sheet and determine the thickness of the negative electrode film. Then, use a scraper to scrape samples from the first and second negative electrode films respectively. The sampling area for the first negative electrode film is the region extending 1 / 3 of the total thickness of the active material layer from the surface of the negative electrode film away from the current collector towards the negative electrode film. The sampling area for the second negative electrode film is the region extending 1 / 3 of the total thickness of the active material layer from the surface of the negative electrode film close to the current collector towards the negative electrode film. Then, soak the samples thoroughly in dimethyl carbonate (DMC) for 12 hours, rinse repeatedly 5-10 times, and dry to obtain powder. Fresh graphite powder can also be used for testing. Specifically, the negative electrode powder sample was coated on a glass slide, and a laser confocal Raman spectrometer (high-precision Renishaw laser confocal Raman spectrometer) was used to scan the sample with an excitation wavelength of 532 nm. The scanning area was 45 μm × 45 μm, divided into 10 × 10 grids, with grid vertices as test points and a step size of 5 μm. The total number of scan points was 1000, thereby obtaining the ID / IG values at different sites. The distribution of all ID / IG values was statistically analyzed to obtain the median L50.
[0078] In this application, the median of ID / IG is a better indicator of the overall crystallinity of graphite than the point value. Calculating the median can reduce the influence of extreme values during the test and improve the confidence of the test results.
[0079] As an example, the median ID / IG value L50 of the first graphite can be 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.405, 0.41, 0.415, 0.42, 0.425, 0.43, 0.435, 0.44, 0.46, 0.48, 0.5, 0.51, 0.52, 0.53, 0.54, 0.55, etc., or can be a range of any of the above values.
[0080] As an example, the median ID / IG value L50 of the second graphite can be 0.05, 0.08, 0.1, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, etc., or can be a range of any of the above values.
[0081] Based on the double-layer coating design of the negative electrode sheet, further adjusting the median ID / IG ratio L50 of the first graphite and the second graphite to be within the above range can increase the lithium intercalation active sites of the first graphite, providing a channel for the rapid insertion and extraction of lithium ions, and further improving the charging capacity of the battery cell; at the same time, the second graphite can reduce the lithium consumption of film formation and improve the cycle performance of the battery cell.
[0082] In some embodiments, the specific surface area of the first graphite is smaller than that of the second graphite. This reduces side reactions between the first graphite and the electrolyte, while the second graphite provides more active sites, improving lithium storage capacity and balancing the cycle life and charging performance of the battery cell.
[0083] In some embodiments, the specific surface area of the first graphite is 0.8 m². 2 / g-1.0m 2 / g.
[0084] In some embodiments, the specific surface area of the second graphite is 1.9 m². 2 / g-2.1m 2 / g.
[0085] By ensuring that the specific surface areas of the first and second graphite are within the aforementioned range, on the one hand, side reactions between the first graphite and the electrolyte can be reduced, and on the other hand, the number of active sites on the surface of the second graphite can be increased, thereby improving the rate of lithium-ion insertion into the graphite and thus balancing the cycle life and kinetic performance of the battery cell.
[0086] In this application, specific surface area has a meaning known in the art and can be tested using methods known in the art. The determination method can refer to GB / T19587-2017, using the nitrogen adsorption specific surface area analysis test method, and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test can be performed using a Tri-Star3020 specific surface area and pore size analyzer from Micromeritics, USA. The negative electrode powder samples used in this test can be either fresh graphite powder or negative electrode sheets obtained by discharging a single battery cell to 0% SOC, disassembling it, observing the cross-section of the sheet using CP-SEM, and calibrating the thickness of the negative electrode film. Then, samples are scraped from the first and second negative electrode films using a scraper. The sampling area for the first negative electrode film is defined as the region extending 1 / 3 of the total thickness of the active material layer from the surface of the negative electrode film away from the current collector towards the negative electrode film. The sampling area for the second negative electrode film is defined as the region extending 1 / 3 of the total thickness of the active material layer from the surface of the negative electrode film close to the current collector towards the negative electrode film. The samples are then thoroughly soaked in dimethyl carbonate (DMC) for 12 hours, rinsed repeatedly 5-10 times, dried, and sintered in a tube furnace at 400°C for 2 hours.
[0087] As an example, the specific surface area of the first graphite can be 0.8 m². 2 / g, 0.83m 2 / g, 0.86m 2 / g, 0.89m 2 / g, 0.92m 2 / g, 0.95m 2 / g, 0.98m 2 / g, 1.0m 2 / g, etc., or a range consisting of any of the above values.
[0088] As an example, the specific surface area of the second graphite can be 1.9 m². 2 / g, 1.93m 2 / g, 1.96m 2 / g, 1.99m 2 / g, 2.02m 2 / g, 2.05m 2 / g, 2.08m 2 / g、2.1m 2 / g, etc., or a range consisting of any of the above values.
[0089] In some embodiments, at least a portion of the surface of the first graphite comprises a carbon material. By coating the surface of the first graphite with a carbon material, the specific surface area of the first graphite can be reduced, side reactions can be decreased, and the charging performance and cycle life of the battery cell can be balanced.
[0090] In some embodiments, the mass percentage of carbon element is 2%-4% based on the total weight of the first negative electrode film layer.
[0091] In this application, the mass percentage of carbon can be tested using the following method: Discharge the battery cell to 0% SOC, disassemble the battery cell to obtain the negative electrode sheet, observe the cross-section of the electrode sheet using in-situ electrochemical scanning electron microscopy (CP-SEM) and determine the thickness of the negative electrode film. Then, use a scraper to scrape the sample to be tested from the first negative electrode film layer. The area extending from the surface of the negative electrode film layer near the current collector towards the negative electrode film layer, representing 1 / 3 of the total thickness of the active material layer, is designated as the sampling area of the first negative electrode film layer. For example, if the CP-SEM observation shows a negative electrode film layer thickness of 75 μm, the area on the surface of the negative electrode film layer near the current collector, with a thickness of 25 μm, is designated as the sampling area of the first negative electrode film layer. Pass the collected sample into air and test the sample using thermogravimetric analysis (TG) to obtain the mass percentage of carbon.
[0092] As an example, the mass percentage of carbon can be 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, etc., or can be a range of any of the above values.
[0093] In some embodiments, the volume average particle size Dv50 of the first graphite is smaller than the volume average particle size Dv50 of the second graphite.
[0094] In some embodiments, the volume average particle size Dv50 of the first graphite is 10 μm-13 μm.
[0095] In some embodiments, the volume average particle size Dv50 of the second graphite is 14 μm-16 μm.
[0096] In this application, the volume average particle size Dv50 of graphite refers to the particle size corresponding to a cumulative volume distribution percentage of 50%, for example, measured using a laser particle size analyzer (Malvern Master Size2000) in accordance with standard GB / T 19077-2024. The specific testing process is as follows: The battery cell is discharged to 0% SOC, then the negative electrode is disassembled and the cross-section of the electrode is observed using CP-SEM to determine the thickness of the negative electrode film. Then, the sample to be tested is scraped from the first negative electrode film and the second negative electrode film respectively using a scraper. The area extending 1 / 3 of the total thickness of the active material layer from the surface of the negative electrode film away from the current collector towards the negative electrode film is taken as the sampling area of the first negative electrode film. The area extending 1 / 3 of the total thickness of the active material layer from the surface of the negative electrode film close to the current collector towards the negative electrode film is taken as the sampling area of the second negative electrode film. Then, the sample is repeatedly shaken and cleaned with dimethyl carbonate (DMC) for 5-10 times. After drying, the sample is sintered in a tube furnace at 400℃ for 2 hours. After sintering, an appropriate amount of the sample to be tested is taken (the sample concentration should be 8%-12% light-blocking degree), deionized water is added, and the sample is ultrasonically dispersed to ensure complete dispersion. Then, the sample is measured according to the GB / T19077-2024 standard.
[0097] As an example, the volume average particle size Dv50 of the first graphite can be 10μm, 10.3μm, 10.6μm, 10.9μm, 11.2μm, 11.5μm, 11.8μm, 12.1μm, 12.4μm, 12.7μm, 13μm, etc., or can be a range of any of the above values.
[0098] As an example, the volume average particle size Dv50 of the second graphite can be 14μm, 14.2μm, 14.4μm, 14.6μm, 14.8μm, 15μm, 15.2μm, 15.4μm, 15.6μm, 15.8μm, 16μm, etc., or can be a range of any of the above values.
[0099] The first type of graphite has a small average particle size, which can shorten the lithium-ion diffusion path, increase the lithium-ion migration rate, and thus improve the charging performance of the battery cell. The second type of graphite has a large average particle size, which can increase the compaction density and mechanical strength of the negative electrode film. It can effectively buffer and disperse the macroscopic mechanical stress generated by the upper fast charging reaction and the overall axial expansion difference, suppress the phenomenon of overall electrode warping after the increase of the size of the high negative electrode film, improve the cycle performance of the battery cell, and take into account the energy density of the battery cell.
[0100] In some embodiments, the compaction density of the negative electrode film is 1.65 g / cm³. 3 -1.75g / cm 3 This can increase the energy density of individual battery cells.
[0101] This application provides a method for testing the areal density and compaction density of the negative electrode film: The battery cell is discharged to 0% SOC, then the negative electrode sheet is disassembled, for example, a single-sided coated negative electrode sheet (if it is a double-sided coated sheet, the negative electrode film layer on one side can be wiped off first), and cut into small circular pieces with an area of S2. The weight is recorded as M3, and the thickness H3 is measured. Then, the negative electrode film layer of the weighed negative electrode sheet is wiped off, the weight of the negative current collector is recorded as M2, and the thickness H2 is measured. The single-sided areal density of the negative electrode film = (M3-M2) / S2, the thickness of the negative electrode film = H3-H2, and the compaction density of the negative electrode film = single-sided areal density of the negative electrode film / thickness of the negative electrode film. To ensure the accuracy of the test results, multiple sets (e.g., 10 sets) of samples can be tested, and the average value is calculated as the test result, with the unit being g / cm³. 3 .
[0102] As an example, the compaction density of the negative electrode film can be 1.65 g / cm³. 3 1.66 g / cm 3 1.67 g / cm 3 1.68g / cm 3 1.69 g / cm 3 1.7g / cm 3 1.71 g / cm 3 1.72g / cm 3 1.73g / cm 3 1.74 g / cm 3 1.75g / cm 3 etc., or a range consisting of any of the above values.
[0103] In some embodiments, the areal density of the negative electrode film layer on one side is 0.135 g / 1540.25 mm. 2 -0.17g / 1540.25mm 2 When the unilateral density of the negative electrode film is within the above-mentioned range, the transport distance of lithium ions in the negative electrode film can be reduced, which is beneficial to improving the charging performance of the battery cell while taking into account the energy density of the battery cell.
[0104] As an example, the areal density of the negative electrode film layer on one side can be 0.135 g / 1540.25 mm. 2 0.14g / 1540.25mm 2 0.145g / 1540.25mm 2 0.15g / 1540.25mm 2 0.155g / 1540.25mm 2 0.16g / 1540.25mm2 0.165g / 1540.25mm 2 0.17g / 1540.25mm 2 etc., or a range consisting of any of the above values.
[0105] In some embodiments, the thickness of the negative electrode film on one side is 50 μm to 70 μm. A thickness within this range can reduce the transport distance of lithium ions within the negative electrode film, which is beneficial for improving the charging performance of the battery cell.
[0106] As an example, the thickness of the negative electrode film on one side can be 50μm, 52μm, 54μm, 56μm, 58μm, 60μm, 62μm, 64μm, 66μm, 68μm, 70μm, etc., or can be a range of any of the above values.
[0107] In some embodiments, the thickness of the first negative electrode film layer on one side is 25μm-35μm.
[0108] As an example, the thickness of the first negative electrode film layer on one side can be 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, etc., or can be any range of the above values.
[0109] In some embodiments, the thickness of the second negative electrode film layer on one side is 25μm-35μm.
[0110] As an example, the thickness of the second negative electrode film on one side can be 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, etc., or can be any range of the above values.
[0111] By keeping the thicknesses of the first and second negative electrode films within the aforementioned range, the lithium-ion transport path can be shortened, improving the fast-charging performance of individual battery cells while maintaining energy density.
[0112] In some embodiments, the size of the negative electrode film layer is 140mm-350mm along the height direction of the battery cell.
[0113] As an example, along the height direction of the battery cell, the size of the negative electrode film can be 140mm, 170mm, 210mm, 240mm, 270mm, 300mm, 330mm, 350mm, etc., or can be a range of any of the above values.
[0114] In some embodiments, the negative electrode film layer comprises carbon nanotubes. The high aspect ratio and three-dimensional network structure of carbon nanotubes can form a conductive framework that runs through the negative electrode film layer, effectively constraining the expansion and contraction deformation of graphite, reducing stress accumulation inside the electrode, and improving the problem of deteriorated lifespan due to electrode expansion during cycling.
[0115] In some embodiments, the carbon nanotubes account for 0.01%-0.1% of the total mass of the negative electrode film. This improves electrode expansion and enhances the cycle performance of the battery cell.
[0116] As an example, based on the total mass of the negative electrode film, the mass percentage of the carbon nanotubes can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, etc., or can be a range of any of the above values.
[0117] In some embodiments, the specific capacity of the negative electrode film is 354 mAh / g-360 mAh / g. Therefore, the lithium intercalation in the negative electrode film is relatively sufficient, resulting in a high specific capacity of the negative electrode material, which can improve the capacity and cycle life of the battery cell. The specific capacity of the negative electrode film in this application can be tested using methods known in the art. As an example, the battery cell is discharged to 0% SOC, the battery cell is disassembled to obtain the negative electrode sheet, the negative electrode sheet is punched into small discs, and then a lithium metal sheet is used as the counter electrode, a polypropylene (PP) film is used as the separator, and an electrolyte is injected. The electrolyte formulation is as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed to obtain an organic solvent with mass percentages of 26.25%, 43.75%, and 17.5%, respectively. Then, LiPF6 is dissolved in the above organic solvent, with a LiPF6 mass percentage of 12.5%. CR2430 coin cells are assembled in an argon-protected glove box. At 25℃, the prepared coin cell was first discharged at a constant current of 0.05 C to 0.005 V, then discharged at a constant current of 10 μA to 0.005 V, and allowed to stand for 5 min. Afterwards, it was charged at a constant current of 0.1 C to 2.0 V, and the charging capacity of the coin cell was recorded. Then, the prepared coin cell was discharged at a constant current of 0.05 C to 0.005 V, then discharged at a constant current of 10 μA to 0.005 V, and the discharge capacity of the coin cell was recorded. The ratio of the discharge capacity of the coin cell to the mass of the graphite negative electrode active material sample is the specific capacity of the graphite negative electrode active material. The negative electrode sheet used in this test can be obtained by discharging the battery cell to 0% SOC, disassembling it, soaking it thoroughly in DMC for 12 h, rinsing it repeatedly 5-10 times, and then drying it.
[0118] As an example, the specific capacity of the negative electrode film can be 354mAh / g, 355mAh / g, 356mAh / g, 357mAh / g, 358mAh / g, 359mAh / g, 360mAh / g, etc., or can be a range of any of the above values.
[0119] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0120] In some embodiments, the negative electrode film layer may optionally include an adhesive. The adhesive may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0121] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, graphene, and carbon nanofibers.
[0122] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0123] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0124] In some embodiments, the lithium fluorinated sulfonylimide includes one or both of lithium bisfluorosulfonylimide and lithium bistrifluoromethylsulfonylimide. Thus, both of these lithium fluorinated sulfonylimide can improve the cycle performance of the battery cell.
[0125] As an example, based on the total mass of the electrolyte, the mass percentage of the lithium fluorosulfonamide can be 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, etc., or can be a range of any of the above values.
[0126] In some embodiments, the lithium fluorosulfonylimide comprises 4%-7% of the total mass of the electrolyte. A mass percentage of lithium fluorosulfonylimide within this range can improve the high-temperature cycle performance of the battery cell.
[0127] In some embodiments, the electrolyte salt further includes lithium hexafluorophosphate. Lithium hexafluorophosphate is more easily dissociated, which can improve the ionic conductivity of the electrolyte and enhance the charging capability of the battery cell at room temperature.
[0128] In some embodiments, the lithium hexafluorophosphate accounts for 8%-13.5% of the total mass of the electrolyte.
[0129] As an example, based on the total mass of the electrolyte, the mass percentage of lithium hexafluorophosphate can be 8%, 9%, 10%, 11%, 12%, 13%, 13.5%, etc., or can be a range of any of the above values.
[0130] In the embodiments of this application, the types and contents of electrolyte salts in the electrolyte are as known in the art and can be detected using equipment and methods known in the art. For example, the electrolyte salts in the electrolyte can be qualitatively or quantitatively analyzed by ion chromatography analysis method with reference to standard JY / T 0575-2020 "General Rules for Ion Chromatography Analysis". In the embodiments of this application, freshly prepared electrolytes can be used as samples, free electrolytes from fresh batteries can be used as samples, or battery cells that have been completely discharged (discharged to the discharge cutoff voltage so that the charge state of the battery cell is about 0% SOC) can be disassembled in reverse and the free electrolyte obtained from the battery cell can be used as samples for detection by ion chromatography analysis method.
[0131] In some embodiments, the electrolyte comprises a carbonate solvent, which includes one or more of ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate. This improves the electrolyte's ability to dissociate electrolyte salts, increases the electrolyte's ionic conductivity, and enhances the charging capability of the battery cell at room temperature.
[0132] In some embodiments, the carbonate solvent accounts for 70%-85% of the total mass of the electrolyte.
[0133] As an example, based on the total mass of the electrolyte, the mass percentage of the carbonate solvent can be 70%, 72%, 74%, 76%, 78%, 80%, 82%, 85%, etc., or can be a range of any of the above values.
[0134] In some embodiments, the electrolyte includes an additive, which includes one or more of vinylene carbonate, fluoroethylene carbonate, trimethyl phosphate, dimethyl methyl phosphate, and biphenyl.
[0135] Ethylene carbonate and fluoroethylene carbonate can form a stable SEI film on the graphite surface, reducing side reactions between the electrolyte and graphite and improving the cycle life of the battery cell.
[0136] Trimethyl phosphate (TMP) captures active protons through phosphorus-containing active particles, inhibiting the thermal decomposition of organic solvents and significantly improving the thermal stability of the electrolyte. It also forms a protective film on the electrode surface, enhancing cycle performance. Dimethyl methyl phosphate (DMP) is a flame retardant additive that significantly improves the thermal stability of the electrolyte through its phosphorus content.
[0137] When a battery cell is overcharged, biphenyl can undergo a polymerization reaction on the surface of the positive electrode, thereby forming a polymer film and generating gas on the surface of the positive electrode active material. This triggers the internal pressure valve of the battery cell to open prematurely, reducing the risk of thermal runaway caused by continuous overcharging and improving the safety of the battery cell.
[0138] In this application, after disassembling the battery cell to obtain the electrolyte, the types and contents of organic components in the electrolyte are known in the art and can be detected using equipment and methods known in the art. For example, GB / T9722-2023 "General Rules for Gas Chromatography of Chemical Reagents" can be referred to to perform qualitative and quantitative analysis of organic components in the electrolyte by gas chromatography.
[0139] In some embodiments, the conductivity of the electrolyte at 25°C is 9 mS / cm-13 mS / cm. This improves the lithium-ion migration rate and enhances the charging performance of the battery cell.
[0140] In this application, the conductivity of the electrolyte at 25°C can be tested using any method known in the art. As an example, refer to HG... T 4067 The 2015 standard for lithium hexafluorophosphate electrolytes requires disassembling battery cells to obtain the electrolyte. Approximately 100 mL of electrolyte sample is taken into a dry, clean, corrosion-resistant sample bottle and placed in a constant-temperature water bath. The sample is shaken periodically and the temperature is maintained at 25°C (with a deviation of ±5°C). After the sample temperature stabilizes, its conductivity is tested using a commercially available conductivity meter. The conductivity meter is cleaned and dried with calibration solution and then vertically placed into the liquid to be tested. The test is started, and the results are recorded after the data has stabilized for more than 10 seconds. The average value is taken after three tests.
[0141] As an example, the conductivity of the electrolyte at 25°C can be 9 mS / cm, 9.5 mS / cm, 10 mS / cm, 10.5 mS / cm, 11 mS / cm, 11.5 mS / cm, 12 mS / cm, 12.5 mS / cm, 13 mS / cm, or a range of any of the above values.
[0142] In some embodiments, the electrolyte injection coefficient of the battery cell is 2.5 g / Ah-2.8 g / Ah.
[0143] Battery cells with an electrolyte injection coefficient within the above range can keep the side reactions between carbonate solvents and negative electrode active materials at a low level, thus ensuring the battery's cycle life; they can also improve the wettability between the electrolyte and the electrode, reduce the battery interface resistance, decrease the battery impedance, and further improve the battery's charging performance.
[0144] The electrolyte filling factor of a battery cell refers to the ratio of the mass of the electrolyte inside the battery cell to the battery capacity. The electrolyte filling factor of a battery cell can be obtained by any method known in the art.
[0145] As an example, the electrolyte injection coefficient of the battery cell can be 2.5g / Ah, 2.55g / Ah, 2.6g / Ah, 2.65g / Ah, 2.7g / Ah, 2.75g / Ah, 2.8g / Ah, etc., or can be a range of any of the above values.
[0146] For example, the test method for the electrolyte injection coefficient of a battery cell includes the following steps: (1) Weigh the battery cell and record the mass as m1. Disassemble the battery cell discharged to 0% SOC in a dry glove box and completely immerse all disassembled components in dimethyl carbonate (DMC). The immersion time can be set as needed, such as 10-20h, e.g., 16h. Pour out the DMC, continue to immerse in DMC and pour out repeatedly, e.g., three times, and then dry and weigh all components. Record the mass as m2. The electrolyte mass is m1-m2, in g. (2) At 25°C, charge the battery cell at a constant current of 0.33C to 3.8V, then charge at a constant voltage to 0.05C, let stand for 5 min, and then discharge at a constant current of 0.33C to 2.0V, let stand for 5 min. This is one discharge cycle. The discharge capacity obtained is taken as capacity F, in Ah. (3) The ratio of the mass of the electrolyte to the capacity of the battery cell is (m1-m2) / F, with the unit being g / Ah. It can be understood that the ratio of the mass of the electrolyte to the capacity of the battery cell can be obtained after disassembling the battery according to the above method, or it can be calculated based on the amount of electrolyte added before the battery cell is prepared and packaged.
[0147] In some embodiments, the electrolyte may optionally include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0148] In some embodiments, the separator includes: a base membrane; a first functional layer located on at least one side of the base membrane, the first functional layer comprising inorganic particles; and a second functional layer located on the side of the first functional layer away from the base membrane, the second functional layer comprising an adhesive. This reduces the contact angle of the electrolyte at the separator-negative electrode interface, further improving electrolyte wettability. This increases the electrolyte absorption capacity at the top of the battery cell while simultaneously increasing the concentration of electrolyte salts in the electrolyte at the top of the battery cell, thereby further improving the cycle life of the battery cell.
[0149] In some embodiments, the inorganic particles include one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide. This improves the wettability of the electrolyte to the separator membrane and enhances the electrolyte retention capacity of the electrode assembly.
[0150] In some embodiments, the binder comprises a fluoropolymer, which includes one or more of polyvinylidene fluoride, polychlorotrifluoroethylene, and polytetrafluoroethylene. Thus, the fluoropolymer can provide suitable adhesion, ensuring stable bonding of the positive electrode, separator, and negative electrode, while preventing shrinkage at high temperatures and powder shedding during cycling, thereby improving the cycle performance of the battery cell.
[0151] In some embodiments, the average particle size of the fluoropolymer particles is 7 μm-15 μm.
[0152] The average particle size of the fluoropolymer particles is within the above range, which can prevent the agglomeration of small-sized inorganic particles, make the inorganic particles uniformly distributed around the binder particles, significantly improve the capillary effect of the membrane functional layer, and enhance the wettability of the electrolyte to the membrane.
[0153] In this application, the average particle size of the fluoropolymer particles can be tested using methods known in the art.
[0154] The battery cells were discharged to 0% SOC, and the separator was removed. Images were acquired under a scanning electron microscope (SEM) using secondary electron mode. An EDS (Energy Dispersive Spectroscopy) instrument was used to perform area scanning of the SEM images. Fluoropolymer particles were identified by detecting the fluorine (F) element. ImageJ software (1.46r, Win64 version) was used to analyze the particles in the SEM images. The specific steps for using ImageJ are as follows: load the SEM image to be analyzed; use the Cellpose plugin to identify the particles, and then manually correct or label them; finally, use ImageJ to read and analyze the data. The "Feret" parameter of the particles obtained from the statistical analysis is used as the particle size. The average particle size is calculated by taking the particle size of 30-100 fluoropolymer particles.
[0155] As an example, the average particle size of the fluoropolymer particles can be 7μm, 8μm, 9μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, etc., or can be a range of any of the above values.
[0156] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes one or more lithium phosphates and their modified compounds. This improves the safety and cycle performance of the battery cell.
[0157] In some embodiments, the lithium-containing phosphate includes one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate.
[0158] In some embodiments, the areal density of the positive electrode film layer on one side is 0.33 g / 1540.25 mm². 2 -0.36g / 1540.25mm 2 This increases the energy density of individual battery cells.
[0159] As an example, the areal density of the positive electrode film layer on one side can be 0.33 g / 1540.25 mm. 2 0.335g / 1540.25mm 2 0.34g / 1540.25mm 2 0.345g / 1540.25mm 2 0.35g / 1540.25mm 2 0.355g / 1540.25mm 2 0.36g / 1540.25mm 2 etc., or a range consisting of any of the above values.
[0160] In some embodiments, the compaction density of the positive electrode film is 2.7 g / cm³. 3 -2.8g / cm 3 This increases the energy density of individual battery cells.
[0161] This application provides a method for testing the areal density and compaction density of the positive electrode film: Discharge the battery cell to 0% SOC, then disassemble the positive electrode sheet, for example, take a single-sided coated positive electrode sheet (if it is a double-sided coated sheet, the positive electrode film layer on one side can be wiped off first), cut it into a small circular piece with an area of S1, weigh it, record its weight as M1, and measure its thickness H1. Then wipe off the positive electrode film layer of the weighed positive electrode sheet, weigh the positive current collector, record its weight as M0, and measure its thickness H0. The single-sided areal density of the positive electrode film = (M1-M0) / S1, the thickness of the positive electrode film = H1-H0, and the compaction density of the positive electrode film = single-sided areal density of the positive electrode film / thickness of the positive electrode film.
[0162] As an example, the compaction density of the positive electrode film can be 2.7 g / cm³. 3 2.71 g / cm 3 2.72 g / cm 3 2.73 g / cm 3 2.74 g / cm 3 2.75g / cm 3 2.76 g / cm 32.77 g / cm 3 2.78g / cm 3 2.79 g / cm 3 2.8g / cm 3 etc., or a range consisting of any of the above values.
[0163] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0164] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0165] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0166] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0167] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0168] In some embodiments, the battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0169] In some implementations, the battery's outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The battery's outer packaging can also be a soft pack, such as a pouch. The soft pack can be made of plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0170] This application does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 The example shown is a square-structured battery cell 5.
[0171] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. The electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0172] In some implementations, the batteries can be assembled into battery modules, and the number of batteries contained in a battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.
[0173] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0174] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0175] The second aspect of this application provides a battery device including the battery cell provided in the first aspect of this application, the battery device including one or more of the following: battery module and battery pack.
[0176] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0177] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0178] A third aspect of this application provides an electrical device, including the battery device provided in the second aspect of this application, wherein the battery device provides electrical energy to the electrical device.
[0179] The electrical device includes at least one of the batteries, battery modules, or battery packs provided in this application. The battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, energy storage systems, etc.
[0180] As the electrical device, a battery, battery module, or battery pack can be selected according to its usage requirements.
[0181] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.
[0182] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell as their power source.
[0183] This application provides an electrical device that uses a battery as a power source. The electrical device can be, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0184] To make the technical problems, technical solutions, and beneficial effects solved by the embodiments of this application clearer, the following will provide a more detailed description in conjunction with the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its applications. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0185] I. Implementation Examples The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0186] Example 1 1. Preparation of negative electrode sheet The second anode slurry was prepared by mixing second graphite, conductive carbon nanotubes (CNTs), styrene-butadiene rubber (SBR) binder, and sodium carboxymethyl cellulose (sodium carboxymethyl cellulose) dispersant in a mass ratio of 96.75:0.05:2.5:0.7 and adding water as a solvent. The median ID / IG ratio (L50) of the second graphite was 0.14, the volume average particle size (Dv50) was 15 μm, and the specific surface area was 2 m². 2 / g.
[0187] First graphite, conductive carbon nanotubes (CNTs), binder styrene-butadiene rubber (SBR), and dispersant sodium carboxymethyl cellulose (Sodium carboxymethyl cellulose) were mixed in a mass ratio of 98.3:0.05:1.0:0.65 and then added to water to prepare the first negative electrode slurry. The first graphite had a median ID / IG ratio (L50) of 0.35, a volume average particle size (Dv50) of 11.8 μm, and a specific surface area of 0.9 m². 2 The first graphite contains carbon on its surface, with a carbon content of 3% based on the total weight of the first graphite. The first and second negative electrode slurries are simultaneously coated on both sides of a 6μm thick copper foil, cold-pressed, and dried. The second negative electrode film is located on both sides of the copper foil, and the first negative electrode film is located on the sides of the second negative electrode film furthest from the copper foil. The thickness of each side of the first and second negative electrode film is 28.8μm. After cutting, a negative electrode sheet is obtained, with a compaction density of 1.7 g / cm³. 3 The specific capacity of the negative electrode film is 358 mAh / g.
[0188] Along the height direction of the battery cell, the negative electrode film has a size of 151 mm, and the height direction is parallel to the direction of gravity.
[0189] 2. Positive electrode plate The positive electrode includes a positive current collector and a positive film layer located on both sides of the aluminum foil of the positive current collector.
[0190] Lithium iron phosphate (LiFePO4), a conductive agent (Super P), a binder (polyvinylidene fluoride (PVDF), and a dispersant (sodium carboxymethyl cellulose) were mixed in a mass ratio of 97.6:0.1:1.8:0.5. The mixture was then thoroughly mixed in the solvent N-methylpyrrolidone (NMP) and coated onto the surface of the positive electrode current collector. After drying, cold pressing, and cutting, the positive electrode sheet was obtained. The areal density of the positive electrode film on one side was 0.34 g / 1540.25 mm². 2 The compaction density of the positive electrode film is 2.75 g / cm³. 3 .
[0191] 3. Separating membrane The base film is a polyethylene film with a thickness of 5 μm. A first functional layer and a second functional layer are disposed on one side of the base film, with the first functional layer located between the base film and the second functional layer.
[0192] The first functional layer includes ceramic particles Al2O3, and the second functional layer includes PVDF particles with a volume average particle size Dv50 of 12 μm.
[0193] 4. Preparation of electrolytes Ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are mixed in a mass ratio of 25:52:23 to form an organic solvent; then, 5% by mass of vinylene carbonate (VC), 0.25% by mass of fluoroethylene carbonate (FEC), 0.25% by mass of trimethyl phosphate, 0.25% by mass of dimethyl methyl phosphate, and 0.25% by mass of biphenyl are added.
[0194] Lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI) were dissolved in the above organic solvent to prepare an electrolyte with a mass ratio of 11.5% LiPF6 and a mass ratio of 5% LiFSI.
[0195] 5. Preparation of battery cells The positive electrode, separator, and negative electrode are stacked in sequence and wound to obtain an electrode assembly. The electrode assembly is placed in a shell, baked, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a battery cell is obtained.
[0196] The preparation methods of the battery cells in Examples 2-5 and Comparative Examples 2-5 are similar to those in Example 1, except that the median ID / IG median L50 of the first graphite and the second graphite used are different. The detailed differences and the test results of the battery cells are shown in Table 1.
[0197] The preparation methods of the battery cells in Examples 6-11 are similar to those in Example 1, except that the volume average particle size Dv50 and specific surface area of the first and second graphite used are different. Detailed differences and test results of the battery cells are shown in Table 2.
[0198] The preparation methods of the battery cells in Examples 12-13 and Comparative Examples 6-7 are similar to those in Example 1, except that the content of electrolyte salt used is different.
[0199] The preparation method of the battery cell in Example 14 is similar to that in Example 1, except that the type of electrolyte salt used is different. Detailed differences and test results of the battery cell are shown in Table 3.
[0200] Example 15 and Comparative Example 1 are prepared using a battery cell in a manner similar to that in Example 1, except that the negative electrode film size is different along the height direction of the battery cell. Detailed differences and test results of the battery cell are shown in Table 4.
[0201] II. Performance Testing 1. High-Temperature Cyclic Life Test Method The 45℃ cyclic test procedure is as follows: The initial capacity C0 of each battery cell was calibrated at room temperature, and then placed in a 45°C incubator. The test voltage range was 2.0V to 3.8V. The cells were charged at a constant current of 1C to 3.44V, then at a constant current of 0.33C to 3.55V, and finally at a constant current of 0.1C to 3.8V. Then, they were discharged at a constant current of 1C to 2.0V, and then at a constant current of 0.33C to 2.0V. After every 100 cycles, the cells were returned to room temperature and the capacity Cn (n = 1, 2, 3, 4, ...) was recalibrated. This cycle was repeated until the capacity retention (F = Cn / C0) reached 80%, and the corresponding number of cycles was recorded.
[0202] 2. 25℃ Charging Performance Test Method The fast charging test procedure is as follows: 1. Allow the battery cell to rest for 30 minutes; 2. Discharge at 0.33C to 2.0V; 3. Allow to rest for 30 minutes; 4. Charge at 2.97C constant current to 15% SOC; 5. Charge at 2.71C constant current to 20% SOC; 6. Charge at 2.46C constant current to 25% SOC; 7. Charge at 2.25C constant current to 30% SOC; 8. Charge at 2.03C constant current to 35% SOC; 9. Charge at 1.74C constant current to 40% SOC; 10. Charge at 1.6C constant current to 45% SOC; 11. Charge at 1.49C constant current to 50% SOC; 12. Charge at 1.45C constant current to 55% SOC; 13. Charge at 1.41C constant current to 60% SOC; 14. 15. Charge at a constant current of 1.32C to 65% SOC; 16. Charge at a constant current of 1.2C to 70% SOC; 17. Charge at a constant current of 1.07C to 75% SOC; 18. Charge at a constant current of 0.94C to 80% SOC; 19. Charge at a constant current of 0.81C to 85% SOC; 20. Charge at a constant current of 0.33C to 3.8V; 21. Charge at a constant current of 0.1C to 3.8V; 22. Let stand for 30 min; 23. Discharge at 0.33C to 2.0V; 24. Let stand for 5 min; Count the charging time from 10% SOC to 80% SOC, in minutes.
[0203] III. Analysis of Test Results for Each Embodiment and Comparative Example Battery cells for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1-4 below.
[0204] Table 1
[0205] As shown in Table 1, with the increase of the median ID / IG ratio (L50) of graphite, the increased internal defects of graphite particles provide more lithium intercalation sites, thus improving the charging capacity of the battery cell. However, with the increase of the median ID / IG ratio (L50), the lithium consumption for SEI film formation and repair increases, the solvation effect is amplified, the risk of graphite layer peeling during cycling increases, and the cycle life of the battery cell decreases. This application achieves a balance between the charging capacity and cycle life of the battery cell by making the median ID / IG ratio (L50) of the first graphite larger than that of the second graphite, while keeping it within a suitable range.
[0206]
[0207] As can be seen from Table 2, by combining first and second graphite with appropriate average particle size and specific surface area, and making the specific surface area of the first graphite smaller than that of the second graphite, the side reactions between the negative electrode active material and the electrolyte can be reduced, thereby improving the cycle performance and charging capacity of the battery cell.
[0208]
[0209] As shown in Table 3, increasing the content of lithium fluorosulfonylimide in the electrolyte can improve the cycle performance and charging capacity of the battery cells. However, further increasing the content of lithium fluorosulfonylimide in the electrolyte does not significantly improve the cycle performance and increases the battery manufacturing cost. This application achieves a balance between the cycle performance and charging performance of the battery cells by combining lithium fluorosulfonylimide within a suitable range with carbonate solvents and additives.
[0210] As can be seen from Example 14, different lithium fluorine sulfonyl imide can all achieve the effect of balancing the charging capacity of the battery cell, thereby improving the cycle performance of the battery cell.
[0211] Table 4
[0212] As shown in Table 4, the volumetric energy density of a single battery cell increases with the increase of the negative electrode film size. However, due to the extended longitudinal diffusion path of lithium ions, the cycle performance decreases, which also affects the charging performance. The embodiments of this application, through the above technical solution, can significantly improve the cycle life of high-energy-density battery cells with a negative electrode film height (i.e., along the height direction of the battery cell) ≥140mm, achieving a balance between high energy density and high cycle life.
[0213] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A battery cell, characterized in that, The device includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The electrolyte comprises an electrolyte salt, which includes lithium fluorosulfonyl imide, and the lithium fluorosulfonyl imide accounts for 3%-8.5% of the total mass of the electrolyte. The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer, and the second negative electrode film layer is disposed between the negative current collector and the first negative electrode film layer. The first negative electrode film layer includes a first graphite, and the median ID / IG ratio L50 of the first graphite is 0.3-0.
55. The second negative electrode film layer includes a second graphite, and the median ID / IG ratio L50 of the second graphite is 0.05-0.
2. Along the height direction of the battery cell, the size of the negative electrode film is greater than or equal to 140 mm, and the height direction is parallel to the direction of gravity.
2. The battery cell according to claim 1, characterized in that, The specific surface area of the first graphite is smaller than that of the second graphite.
3. The battery cell according to claim 1 or 2, characterized in that, The specific surface area of the first graphite is 0.8 m². 2 / g-1.0m 2 / g; and / or, the specific surface area of the second graphite is 1.9m². 2 / g-2.1m 2 / g.
4. The battery cell according to any one of claims 1-3, characterized in that, At least a portion of the surface of the first graphite comprises carbon material.
5. The battery cell according to claim 4, characterized in that, Based on the total weight of the first negative electrode film layer, the mass percentage of carbon element is 2%-4%.
6. The battery cell according to any one of claims 1-5, characterized in that, The volume average particle size Dv50 of the first graphite is smaller than that of the second graphite.
7. The battery cell according to claim 6, characterized in that, The volume average particle size Dv50 of the first graphite is 10 μm-13 μm; and / or, the volume average particle size Dv50 of the second graphite is 14 μm-16 μm.
8. The battery cell according to any one of claims 1-7, characterized in that, The compaction density of the negative electrode film is 1.65 g / cm³. 3 -1.75g / cm 3 .
9. The battery cell according to any one of claims 1-8, characterized in that, The areal density of the negative electrode film layer on one side is 0.135 g / 1540.25 mm. 2 -0.17g / 1540.25mm 2 .
10. The battery cell according to any one of claims 1-9, characterized in that, The thickness of the negative electrode film on one side is 50μm-70μm.
11. The battery cell according to any one of claims 1-10, characterized in that, The thickness of the first negative electrode film layer on one side is 25μm-35μm; and / or the thickness of the second negative electrode film layer on one side is 25μm-35μm.
12. The battery cell according to any one of claims 1-11, characterized in that, Along the height direction of the battery cell, the size of the negative electrode film is 140mm-350mm.
13. The battery cell according to any one of claims 1-12, characterized in that, The negative electrode film layer includes carbon nanotubes.
14. The battery cell according to claim 13, characterized in that, Based on the total mass of the negative electrode film, the mass percentage of the carbon nanotubes is 0.01%-0.1%.
15. The battery cell according to any one of claims 1-14, characterized in that, The specific capacity of the negative electrode film is 354mAh / g-360mAh / g.
16. The battery cell according to any one of claims 1-15, characterized in that, The fluorinated sulfonyl imide lithium includes one or both of lithium bisfluorosulfonyl imide and lithium bistrifluoromethylsulfonyl imide.
17. The battery cell according to any one of claims 1-16, characterized in that, Based on the total mass of the electrolyte, the mass percentage of the lithium fluorinated sulfonamide is 4%-7%.
18. The battery cell according to any one of claims 1-17, characterized in that, The electrolyte salt also includes lithium hexafluorophosphate.
19. The battery cell according to claim 18, characterized in that, Based on the total mass of the electrolyte, the lithium hexafluorophosphate accounts for 8%-13.5% of the total mass.
20. The battery cell according to any one of claims 1-19, characterized in that, The electrolyte includes carbonate solvents, which include one or more of the following: ethylene carbonate, propylene carbonate, butene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and dibutyl carbonate.
21. The battery cell according to claim 20, characterized in that, Based on the total mass of the electrolyte, the carbonate solvent accounts for 70%-85% of the total mass.
22. The battery cell according to any one of claims 1-21, characterized in that, The electrolyte includes additives, which include one or more of vinylene carbonate, fluoroethylene carbonate, trimethyl phosphate, dimethyl methyl phosphate, and biphenyl.
23. The battery cell according to any one of claims 1-22, characterized in that, The conductivity of the electrolyte at 25℃ is 9mS / cm-13mS / cm.
24. The battery cell according to any one of claims 1-23, characterized in that, The electrolyte injection coefficient of the battery cell is 2.5g / Ah - 2.8g / Ah.
25. The battery cell according to any one of claims 1-24, characterized in that, The isolation membrane comprises: Base film; A first functional layer is located on at least one side of the base film, and the first functional layer comprises inorganic particles; A second functional layer is located on the side of the first functional layer away from the base film, and the second functional layer includes an adhesive.
26. The battery cell according to claim 25, characterized in that, The inorganic particles include one or more of the following: silicon dioxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium dioxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide.
27. The battery cell according to claim 25 or 26, characterized in that, The adhesive comprises a fluoropolymer, which includes one or more of polyvinylidene fluoride, polychlorotrifluoroethylene, and polytetrafluoroethylene.
28. The battery cell according to any one of claims 25-27, characterized in that, The average particle size of the fluoropolymer particles is 7μm-15μm.
29. The battery cell according to any one of claims 1-28, characterized in that, The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes one or more of lithium phosphate and its modified compounds.
30. The battery cell according to claim 29, characterized in that, The lithium-containing phosphate includes one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate.
31. The battery cell according to claim 29 or 30, characterized in that, The areal density of the positive electrode film layer on one side is 0.33 g / 1540.25 mm. 2 -0.36g / 1540.25mm 2 .
32. The battery cell according to any one of claims 29-31, characterized in that, The compaction density of the positive electrode film is 2.7 g / cm³. 3 -2.8g / cm 3 .
33. A battery device, characterized in that, The battery device includes any one of the battery cells according to claims 1-32, and the battery device includes one or more of the following: battery module and battery pack.
34. An electrical appliance, characterized in that, Includes the battery device of claim 33, wherein the battery device provides electrical energy to the electrical device.